The Implementation of Real Options Approach in Building Design - Csapi, Vivien; Ratting, Anita (The Hungarian Journal of Marketing and Management, 2019)
The uncertainties surrounding architecture projects, the irreversibility of investment costs and the timing flexibility of the investments together make these projects a highly interesting field for real options theory. The aim of our paper is to highlight the uncertainty and flexibility characteristics of building design, building operations and the possible implications of real options theory. The identification of risk is the key in making sustainable building projects more attractive for investors. Although there are examples for flexible building design, which verify the value creation potential of flexibility, we need a new framework for embedding flexibility in building design. We believe, and prove with our paper that real options theory can provide this framework. A flexible, real options based design can decrease risk surrounding sustainable building design, and enforce value creation.